Förskolepersonals syn på att uppmärksamma särskild begåvning i förskolan - Malin Ekesryd Nordström (Utbildning & Lärande, 2021)
Early attention of giftedness is argued to support continued development and learning for gifted children. The focus of this article is therefore on investigating preschool personnel’s perceptions on giftedness and gifted children. Data was produced using a nationwide online survey, including personnel from eleven Swedish preschools (N = 78). The questions spanned between suggestions for their own descriptions of giftedness, views on support for gifted children, to who in the work team they consider should be responsible for adaptations and support for gifted children. The main conclusions from the survey reveals a lack of education of giftedness among the respondents. Furthermore, a majority of the preschool personnel believe that gifted children have the right to be noted in preschool settings, but few have suggestions on how this should be conducted. The respondents had high confidence that their own preschools were sufficient to meet the needs of gifted children, but the obstacles described were lack of time, lack of suitable teaching materials and that the group sizes were too large. Further conclusions are that principals have an important role on drawing attention to giftedness in preschool settings and that there is a need for more research in this area.